Prospects for a multi-TeV gamma-ray sky survey with the LHAASO water Cherenkov detector array *Supported by National Natural Science Foundation of China (11761141001, 11635011, 11873005). The LHAASO project is supported by the National Key R & D Program of China (2018YFA0404200), the Chinese Academy of Sciences, the Key Laboratory of Particle Astrophysics, IHEP, CAS. (June 2020) - Aharonian, F.; Alekseenko, V.; An 安, Q. 琪; Axikegu,; Bai 白, L.X. 立新; Bao 包, Y.W. 逸炜; Bastieri, D.; Bi 毕, X.J. 效军; Cai 蔡, H. 浩; Cao 曹, Zhe 喆; Cao 曹, Zhen 臻; Chang 常, J. 进; et al.
Abstract: The Water Cherenkov Detector Array (WCDA) is a major component of the Large High Altitude Air Shower Array Observatory (LHAASO), a new generation cosmic-ray experiment with unprecedented sensitivity, currently under construction. WCDA is aimed at the study of TeV -rays. In order to evaluate the prospects of searching for TeV -ray sources with WCDA, we present a projection of the one-year sensitivity of WCDA to TeV -ray sources from TeVCat using an all-sky approach. Out of 128 TeVCat sources observable by WCDA up to a zenith angle of, we estimate that 42 would be detectable in one year of observations at a median energy of 1 TeV. Most of them are Galactic sources, and the extragalactic sources are Active Galactic Nuclei (AGN).